Memorias montoneras: metáforas de la guerra en Argentina - Nofal, Rossana (2024)
The author presents an analysis of Sergio Pollastri’s novel from the critical perspective of the possibilities and impossibilities of the reconstruction of a story, from this testimonial account that is conducted in the territory of violence and weapons (the political militancy) and in the realm of subjectivity (poetry, fiction). It stresses the links between life and literature, which are present throughout the entire novel; therefore, it appeals to metaphor in order to refer to two types of silence in the fictions about revolutionary violence: the option for weapons and the divulgation of information under torture. It highlights the role of the metaphor in this text that stretches the testimonial gender to its limits, and which gains more force towards the end: «The revolution is fragile and superficial as a violet; that which the comparison develops is at the same time what muffles the fall of the brutal leap to the empty space with which the novel ends its enunciation».